104. Evaluation of a Prep Referral System: From Sexual Health Center to Federally Qualified Health Center Prep Clinic. (31st December 2020) - Lillis, Rebecca A; Beckford, Jeremy; Fegley, Joshua; Siren, Julia; Hinton, Bruce; Gomez, Samuel J; Taylor, Stephanie N; Butler, Isolde; Halperin, Jason; Clement, Meredith E
Abstract: Background: In the United States, less than one-quarter of those who are eligible for pre-exposure prophylaxis (PrEP) have been prescribed the medication. Innovative strategies of PrEP delivery are needed to facilitate access and overcome barriers to care. The objective of this study was to evaluate the referral process from a sexual health center (SHC) to a co-located PrEP clinic as an alternative model of PrEP care. Methods: An initial report was generated from the electronic health record (EHR) to determine the number of patients seen at the SHC in 2019. Charts were then manually reviewed to determine whether a PrEP clinic referral was made. For those referred, we determined the method of the referral: PrEP clinic navigator met the patient at the SHC ( handoff ), the navigator was messaged in the EHR to then schedule the appointment ( EHR message ), or the patient was provided a card with the navigator's contact information ( card ). We also determined whether patients had subsequent visits at the PrEP clinic or SHC. Results: From January to December 2019, there were 3570 unique patients seen at the SHC, and 240 (6.7%) were referred to the PrEP clinic. Of 240 referred patients, median age was 29 years; 95 (40%) were non-Hispanic Black and 25 (11%) were Latinx. The majority (n=198, 83%) were male, 32 (13%) were cisfemale, and 9 (4%) were transfemale. An STI was diagnosed on the day of the clinic visit for 116 (49%) patients. Of those who were MSM, 75 (51%) had been diagnosed with an STI in the previous 6 months. In total, 106 referred patients attended an initial PrEP visit and the proportion attending the visit by method of referral was 81%, 38%, and 22% for handoff, EHR message, and card, respectively (p< .0001). Of the 108 patients who attended an initial PrEP visit, 66 (61%) had a subsequent PrEP visit. Of those who did not attend a PrEP visit, 36 (27%) had a subsequent visit at the SHC. Figure 1. Method of Referral from SHC to PrEP Clinic Conclusion: Despite co-location of these two clinics, there are significant drop-offs along the PrEP care continuum for this referral system. Navigator-facilitated handoff was the most effective method of referral from SHC to PrEP Clinic, but further efforts are needed to understand barriers to referral. Implementation of rapid PrEP provided at the SHC may be one possible solution to engaging additional patients in PrEP services. Disclosures: Meredith E. Clement, MD, FHI360 (Consultant)Gilead (Research Grant or Support)Janssen (Scientific Research Study Investigator)